Vráble, Slowakei: Herausbildung und Niedergang des frühbronzezeitlichen Siedlungszentrums – Untersuchungen zu Wirtschaft, Sozialstruktur und politischer Organisation eines Sozialverbandes und seines Umfeldes - Rassmann, Knut (e-Forschungsberichte des DAI, 2023)
The Early Bronze Age fortified settlement of Fidvár by Vráble is located in southwestern Slovakia. Rich resources of fertile loess soil areas, highly valuable copper, gold and tin deposits as well as the area’s function as a cultural interface between central and southeastern Europe over many periods of time emphasize the importance of the landscape. Starting in 2007, an interdisciplinary project has focused on the genesis of the fortified settlement in the context of its surrounding archaeological landscape. Key questions concentrate on the role of early metallurgy, the impact of this proto-urban centre on the environment and the reasons for its formation and decline.